Working Memory 2020
DOI: 10.1093/oso/9780198842286.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Theories of Working Memory

Abstract: Multiple theories of working memory are described in the chapters of this book and often these theories are viewed as being mutually incompatible, yet each is associated with a supporting body of empirical evidence. This chapter argues that many of these differences reflect different research questions, different levels of explanation, and differences in how participants perform their assigned tasks in different laboratories, rather than fundamental theoretical adversity. It describes a version of a multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 111 publications
2
42
0
1
Order By: Relevance
“…One aspect of the bootstrapping phenomenon that does need to be addressed in theoretical descriptions of WM is the fact that over multiple different occasions, and now in both learning and immediate serial recall versions of the task, it is clearly the case that when verbal memory capacity is exhausted, VSM systems can bootstrap performance, an observation that is consistent with recent ideas from other fields of WM research. 44,45 At some level, this observation must argue for some separa-tion between visuospatial and verbal memory processing in tasks that involve WM, and, therefore, would tend to lend itself to the case for specialized visual-spatial STM and to argue contrary to some recent claims. 33 The present study was focused on asking questions about the relation of spatialization and longterm learning.…”
Section: Discussionmentioning
confidence: 93%
“…One aspect of the bootstrapping phenomenon that does need to be addressed in theoretical descriptions of WM is the fact that over multiple different occasions, and now in both learning and immediate serial recall versions of the task, it is clearly the case that when verbal memory capacity is exhausted, VSM systems can bootstrap performance, an observation that is consistent with recent ideas from other fields of WM research. 44,45 At some level, this observation must argue for some separa-tion between visuospatial and verbal memory processing in tasks that involve WM, and, therefore, would tend to lend itself to the case for specialized visual-spatial STM and to argue contrary to some recent claims. 33 The present study was focused on asking questions about the relation of spatialization and longterm learning.…”
Section: Discussionmentioning
confidence: 93%
“…The present multicomponent theory differs from the classical ones in that it is assumed that the central executive is the name for multiple specialized systems or mental tools that can operate together in an integrated way in the healthy brain to support task performance and can be impaired selectively following focal brain damage. Not all such central executive processes have been clearly identified yet through research (e.g., Logie, 2016; Logie, Belletier, & Doherty, in press). The other two theories (described below) also refer to executive processes, with less confidence that the field has enough knowledge to say whether it is composed of closely related or separate components.…”
Section: Our Extended Adversarial Collaboration On Working Memorymentioning
confidence: 99%
“…Originally, a central executive was proposed as a domain-general processing and control mechanism that coordinated the functioning of the short-term memory systems ( Baddeley, 1986 ). Subsequently, a number of separate executive functions were proposed, including inhibition, updating, task switching, and dual-tasking ( Miyake et al, 2000 ) and these have been suggested to be emergent properties of how different cognitive systems interact and are deployed to meet task requirements (see Logie, 2016 ; Logie et al, in press-a ). Thus, according to the multiple-component account, storage and processing can, under certain circumstances, run in parallel, with little-to-no conflict between the demands.…”
Section: The Current Studymentioning
confidence: 99%
“…According to the multiple-component view of working memory outlined by Logie (2011 , 2016 ; Logie et al, in press-a ), serial-ordered recall for visually presented letters at span reflects the use of phonological codes and a phonological rehearsal process. Memory is assumed to be supplemented by a passive visual code for visually presented letters and activated representations of the letters stored in long-term memory ( Logie et al, 2016 ).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation